Modern terrorism between US and Israeli targets and the weakening of the Arab world (International Journal of Scientific Research and Management (IJSRM), 2019)
The purpose of this study is to illustrate the phenomenon of modern terrorism between American and Israeli objectives and to weaken the Arab world. And the study focused on the central question: “How does America and Israel seek to weaken the Arab world through modern terrorism? “,This study answered the main question and the questions came out of it , and in this study we used analytical descriptive method , therefore we got several conclusions , and the important of these are, First , there is no clear and limit definition for terrorism , second , America and Israel used terrorism to achieve objectives in the region , Third , leave the region in permanent conflict to reach weakness state.